Efficacy of hemoperfusion with Seraph-100 in series with single pass albumin dialysis in acute hepatitis B infection: A case report. Issue 2 (February 2023) - Piscitani, Luca; Leone, Silvia; Di Biase, Jessica; Salvati, Lia; Sirolli, Vittorio; Tunno, Marilena; Bonomini, Mario
Acute and acute-on-chronic liver failure is a cause of death in patients suffering from viral hepatitis, and many cases need liver transplantation. Infection from hepatitis B virus may range from asymptomatic to severe acute and fulminant hepatitis. In this setting, treatment is mainly supportive as there is no consensus on antiviral therapy based on non-nucleoside reverse transcriptase inhibitors. Single-pass albumin dialysis is a liver-support technique for patients suffering from liver failure, that has shown effectiveness in the removal of both water-soluble and albumin-bound toxins, which accumulate due to impairment of the liver's cleansing function. We report here the case of a 62-year-old male who presented with a severe acute hepatitis B infection, liver failure, and marked hyperbilirubinemia. Treatment with single-pass albumin dialysis combined with a hemoperfusion device was successful in improving clinical, physiological, and laboratory parameters.